Three Indian siblings affected with progressive myoclonic epilepsy due to unverricht-Lundborg disease - Kavita Srivastava; Bina Mahendrasinh Thakor; Shuvendu Roy; Surekha Rajadhyaksha; Chaitanya Datar (Wolters Kluwer Medknow Publications, 2022)
Background: Progressive myoclonus epilepsy (PME) is a group of heterogeneous genetic disorders characterized by action myoclonus, epileptic seizures, and progressive neurologic deterioration with onset of symptoms in adolescence and adulthood. Unverricht-Lundborg disease (ULD) is the most common type of PME in high-income countries; however, it is under-reported from India due to challenges in clinical recognition and establishment of diagnosis due to lack of availability of genetic studies. Clinical Description: We herewith report three siblings (two girls and a boy) born out of a third-degree consanguineous marriage, with onset of "difficult-to-treat" seizures since early adolescence, with concurrent action myoclonus and ataxia. All three had a waxing and waning course. Electroencephalography exhibited generalized spike-wave and polyspike-wave discharges with photosensitivity while neuroimaging was normal. Management and Outcome: The possibility of PME was considered in view of the clinical phenotype and strong family history. Following detailed elicitation of history, focused physical examination, and rational investigative work-up specific molecular genetic testing were planned for ULD. This showed homozygous expansion of dodecamer (set of 12 nucleotides) repeat in the cystatin B gene in all the three affected siblings. The parents were heterozygous carriers. Genetic counseling was undertaken and anticonvulsant drugs (ACDs) modified accordingly. The definitive diagnosis helped in accurate prognostication and management to improve the quality of life of all three siblings. Conclusion: Clinicians should consider a specific epilepsy syndrome in patients with onset of symptoms in adolescence. ULD is a type of PME with a relatively better course of illness. Establishing the diagnosis has implications on the extent of investigative workup, choice of ACD, and prognosis.